guidelines for the transition of curriculum Agricultural Technology program of UCLA (Revista Electrónica REDINE, 2018)
The Institutional curriculum guidelines are general guidelines for processes, designs and curricular conceptions governing the construction of the curriculum of academic programs. On this basis, the objectives are to detail the academic and administrative mechanisms of transition curriculum Superior Career Technology of Agricultural University " Lisandro Alvarado “, guaranteeing the existence of a unique curriculum design , avoiding the existence of parallel designs , include the Community Service and adapt the curriculum to Teaching Academic Policies and Regulations Curricular Designs University " Lisandro Alvarado " . A diagnosis of the situation of actual implementation of the plan and workshops for the design of the proposal resulting curriculum guidelines  in which the transition to the new plan based study.
Keywords: curriculum guidelines; curriculum; community service